Health Sector Stock Performance Model On The Indonesian Stock Exchange: Model Kinerja Saham Sektor Kesehatan di Bursa Efek Indonesia - Erna Garnia; Siti Riyyan Lisaumi; Nadya Fitriana (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines the performance of the health sector index listed on the Indonesia Stock Exchange (IDX) during the leadership of Susilo Bambang Yudhoyono (SBY, 2004–2014) and Joko Widodo (JKW, 2014–2024), analyzing monthly data comprising eight stock observations. This research is novel for three reasons: First, it uses an Arbitrage Pricing Theory (APT) model with a separate analysis for high- and low-return categories. Second, it systematically compares the influence of seven macroeconomic factors (global indices, macroeconomic indicators, world oil prices, China indices, Arab indices, competitive resources, and inflation) across two distinct government periods. Third, it validates the accuracy of the model using Mean Absolute Deviation (MAD), offering a methodological advancement in stock performance analysis. The results show that, during the SBY administration, all macroeconomic factors significantly influenced stock returns in both the high- and low-return categories. Conversely, during the JKW administration, macroeconomic factors did not simultaneously significantly influence either high or low returns. These findings provide new empirical evidence regarding the sectoral responsiveness of healthcare stocks to macroeconomic factors under different Indonesian governments, and policymakers should recognize that the healthcare sector's responsiveness to macroeconomic factors varies significantly across political leadership.